Evaluation of Antihypertensive Drug Use in Chronic Kidney Failure Patients on Hemodialysis at RSUD A.M. Parikesit Tenggarong: Evaluasi Penggunaan Obat Antihipertensi pada Pasien Gagal Ginjal Kronis dengan Hemodialisis di RSUD A.M. Parikesit Tenggarong - Indriani, Gina Nabila; Hajrah; Ahmad, Islamudin (B-Creta Publisher, 2025)
Hypertension is common in patients with chronic kidney disease on hemodialysis and can be the main cause of death, so antihypertensive drugs are needed. Accurate antihypertensive dosage, especially for drugs that are excreted through the kidneys, is necessary to achieve therapeutic effectiveness and minimize the incidence of toxicity. This study aims to determine patient characteristics, drug use patterns, and appropriate use of antihypertensive doses. Observational research method with retrospective data collection based on outpatient medical records in January-December 2023 using purposive sampling. Of the total 14 patients, most patients were male (58.82%). Most patients were in the early elderly category (46-55 years) (50%). Based on the diagnosis of the disease with the highest percentage, stage 5 chronic kidney disease as the main diagnosis (100%), congestive heart failure as a secondary diagnosis (21.42%), hypertension as a comorbidity (57.14%), and anemia as a complication (100%). The monotherapy antihypertensive drug that is widely used is furosemide (64.28%). Meanwhile, the combination of antihypertensive drugs used was furosemide + telmisartan (7.14%). Evaluation of antihypertensive drugs use obtained 100% according to the dose.